The Effectiveness of Oxytocin Massage Using Lemongrass Oil on Breast Milk Production in Post Partum Mother - Nur Ain Tahir; St. Surya Indah Nurdin; Fidyawati Aprianti A. Hiola; Nour Arizza Dwi Melani (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2025)
Exclusive breastfeeding coverage in Indonesia remains at 63.9%, below the SDGs target 80%, largely due to non-optimal breast milk production. Non-pharmacological methods, such as oxytocin massage, may enhance milk production, and its effectiveness can be increased with lemongrass of oxytocin massage with lemongrass oil on breast milk production in postpartum women. This study was conducted in Tilongkabila subdistrict, Bone Bolango, using a quasi-experimental pretest–posttest design with a control group method, involving 24 postpartum women selected purposively and divided into an intervention group and a control group. The intervention was carried out for five consecutive days, involving measurement of breast milk volume using a manual pump and a self-report questionnaire for mothers. The Mann-Whitney analysis showed a significant increase in breast milk volume in the intervention group compared to the control group (p < 0.05). Mothers received oxytocin massage using lemongrass oil demonstrated greater and more consistent milk production, alongside improved relaxation and comfort. It can be concluded that oxytocin massage using lemongrass oil is effective in increasing breast milk production in postpartum women and can be recommended as a simple, affordable, and safe complementary therapy to support the success of the exclusive breastfeeding program.